Young marriage, parenthood and divorce - Crivello, G; Mann, G (Young Lives, 2020)
This report presents emerging evidence from the Young Marriage and Parenthood Study (YMAPS), a comparative qualitative study of marriage, cohabitation, parenthood and divorce among marginalised adolescents and young people in Ethiopia, India (in the states of Andhra Pradesh and Telangana), Peru and Zambia between 2017 and 2020.